Challenges and Opportunities in Establishing a Collegiate Mentoring Program - Emily Rickerson; Matthew Ohlson; Kate Fogarty; Muthusami Kumaran (EDIS)
Developing a new program can present many challenges at any level. This 2-page fact sheet describes a number of challenges that arise at various stages of developing a mentoring program. Written by Emily Rickerson, Matthew Ohlson, Kate Fogarty, and Muthusami Kumaran, and published by the UF Department of Family Youth and Community Sciences, August 2011. (Photo © C.A.M.P. Gator)